2015
DOI: 10.1016/j.neurobiolaging.2014.07.048
|View full text |Cite
|
Sign up to set email alerts
|

White matter hyperintensities and normal-appearing white matter integrity in the aging brain

Abstract: White matter hyperintensities (WMH) of presumed vascular origin are a common finding in brain magnetic resonance imaging of older individuals and contribute to cognitive and functional decline. It is unknown how WMH form, although white matter degeneration is characterized pathologically by demyelination, axonal loss, and rarefaction, often attributed to ischemia. Changes within normal-appearing white matter (NAWM) in subjects with WMH have also been reported but have not yet been fully characterized. Here, we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

23
221
3
6

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 223 publications
(253 citation statements)
references
References 36 publications
(52 reference statements)
23
221
3
6
Order By: Relevance
“…These results demonstrate that WMH have reduced integrity compared with NAWM, and that NAWM deteriorates with increasing WMH and age, confirming that NAWM in the presence of even a few WMH is not 'normal'. 18 Furthermore, a high-WMH burden in younger people indicates advancing damage in NAWM and should sound alarm bells to identify remediable causes.…”
Section: Discussionmentioning
confidence: 99%
“…These results demonstrate that WMH have reduced integrity compared with NAWM, and that NAWM deteriorates with increasing WMH and age, confirming that NAWM in the presence of even a few WMH is not 'normal'. 18 Furthermore, a high-WMH burden in younger people indicates advancing damage in NAWM and should sound alarm bells to identify remediable causes.…”
Section: Discussionmentioning
confidence: 99%
“…Consistent with our previously published data, 21 there was no change in MD detected in our model, which is somewhat unexpected as MD is a marker of white matter damage in SVD in humans. 27 A recent study has also shown that other DTI measures (AD and RD) may be sensitive to the effects of cerebral hypoperfusion, and for future studies, these additional measures would be advisable to study. 28 Notably, in the same animals in which imaging was conducted, we observed myelin and axonal disruption alongside a prominent inflammatory response.…”
Section: Discussionmentioning
confidence: 99%
“…There is not, for instance, a consensus on the explanation for the relation between WMH presence and growth and reduced cognitive ability; a recent review discusses possibilities ranging from WMHs damaging important neural networks, disrupting neurotransmitters such as those involved in the cholinergic system, or merely acting as an indicator of poorer vascular health, which may impair cognitive ability for other reasons [Prins and Scheltens, 2015]. Further insights into the cytoarchitecture of WMH and the accompanying changes in so‐called normal appearing white matter are provided in Muñoz Maniega et al [2015] and in Wardlaw et al [2015]. It is possible that multiple mechanisms operate and interact: it is unlikely that any one single mechanism is responsible for the loss of complex cognitive abilities.…”
Section: Discussionmentioning
confidence: 99%